Case Study: Pain Management in Postoperative CABG Patient in General Intensive Care Unit - Vanessa Zian Mentari; Urip Rahayu (Universitas Padjadjaran, 2022)
Acute pain is a significant manifestation in postoperative Coronary Artery Bypass Graft (CABG) patients. A sternotomy performed in open-heart surgery is a major cause of postoperative pain. Prolonged postoperative pain can lead to increased the use of analgesics, reduce infection resistance, delayed wound healing after surgery, and extended hospitalization. This study aims to evaluate pain management interventions in the form of deep breathing techniques and collaboration in administering morphine to acute pain in postoperative CABG patients. The method of this study is a case study. The sample of this study is a 69-year-old postoperative CABG patient who complained of chest pain in the chest and incision wound on a scale of 7 (0-10) in General Intensive Care Unit (GICU). Patients describe the pain as stabbing in the chest and getting worse when coughing, eating, and talking. After three days of intervention, the patient experienced a decrease in pain levels. This condition is seen from the decrease in pain levels to a scale of 2 (0-10), the patient's face appears relaxed, the patient does not appear restless, vital signs are within the normal range, and the patient can perform deep breathing techniques by himself when the pain is felt. Pain management through deep breathing techniques and collaboration on morphine administration can reduce acute pain in postoperative CABG patients. Researchers recommend pain management through deep breathing techniques and collaboration on morphine administration to treat acute pain in postoperative CABG patients.